3y-3+9=8y+6-5y

Simple and best practice solution for 3y-3+9=8y+6-5y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3y-3+9=8y+6-5y equation:


Simplifying
3y + -3 + 9 = 8y + 6 + -5y

Reorder the terms:
-3 + 9 + 3y = 8y + 6 + -5y

Combine like terms: -3 + 9 = 6
6 + 3y = 8y + 6 + -5y

Reorder the terms:
6 + 3y = 6 + 8y + -5y

Combine like terms: 8y + -5y = 3y
6 + 3y = 6 + 3y

Add '-6' to each side of the equation.
6 + -6 + 3y = 6 + -6 + 3y

Combine like terms: 6 + -6 = 0
0 + 3y = 6 + -6 + 3y
3y = 6 + -6 + 3y

Combine like terms: 6 + -6 = 0
3y = 0 + 3y
3y = 3y

Add '-3y' to each side of the equation.
3y + -3y = 3y + -3y

Combine like terms: 3y + -3y = 0
0 = 3y + -3y

Combine like terms: 3y + -3y = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| Z^2+11z+24= | | 72x^3+32x^4-16x^5=0 | | 12b^3-9b^2=0 | | a^2-3a-40=0 | | X^3-3y^3z^2= | | a^2+2a-17=-2 | | 8x^2+22x+121=0 | | 5x=2(3+x) | | 7x=3x^2-6 | | (x)*(x^2+3)=35 | | (b+3)(b-6)=0 | | x^3+3x-35=0 | | 5x^2+11x=-2 | | 3m-35=21+14m | | 7x+12y=200 | | 4x^2=21x-5 | | 3m-35=12+4m | | 7(x-7)=126 | | -6(10-4x)=-3(-12-8x) | | -6y-14=7y+25 | | 2(2y-1)-2(2y)=2 | | x(5x-8)=13 | | 3x-9x^3= | | B=9-a | | 3x(x+1)=(2x+3)(x+1) | | -225T+T=T | | 2x^6+8x^4-6xy^2= | | T=9(5T)2 | | -225T+T=225T+-225T | | 3(b-2)-b=5b+12 | | Y=3y^2+15y-18 | | Z^2+13z+30= |

Equations solver categories